Influence of Biochar-Reinforced Hydrogel Composites on Growth and Biochemical Parameters of Bean Plants and Soil Microbial Activities under Different Moisture Conditions - Concepción García-Gómez; Yağmur Uysal; Zeynep Görkem Doğaroğlu; Dimitrios Kalderis; Dionisios Gasparatos; María Dolores Fernández (Agriculture, 2024)
Hydrogels have shown promise in improving soil quality and alleviating plant drought stress. This study investigated the effectiveness of four hydrogel composites composed of polyvinyl alcohol, sodium alginate, and pine or olive tree biochar in improving bean (Phaseolus vulgaris) plant growth and soil microbial activities. The experiment was conducted in natural soil, where biochar–hydrogel composites were applied at a concentration of 0.75% hydrogel per soil weight (w/w) for 35 days under two different moisture conditions: adequate moisture (70% of water holding capacity (WHC)) and drought stress (40% WHC). The results showed variation between hydrogel composites and, more importantly, between water regimes. Under water deficit conditions, biochar–hydrogel composites consistently caused a decrease in plant weight and in chlorophyll (CHL) CHLa/CHLb ratio. Furthermore, antioxidant enzyme activities and malondialdehyde and protein levels generally increased in contrast to the observations at 70% WHC. Regarding microbial activities, the composites reduced soil respiration (12–38%) while promoting phosphatase activity (42–65%) under both moisture regimes. Overall, the introduction of hydrogel composites did not show consistently positive effects on either plants or soil microorganisms. To thoroughly evaluate the efficacy of these hydrogels as soil amendments, further studies are needed, considering different soil types, plant species, and hydrogel application rates.